Ethics in corporate research and development: can responsible research and innovation approaches aid sustainability?. (1st December 2019) - Stahl, Bernd Carsten; Chatfield, Kate; Ten Holter, Carolyn; Brem, Alexander
Abstract: An increase in the number of companies that publish corporate social responsibility (CSR) statements, and a rise in their 'sustainability' research, reflects a growing acceptance that broad ethical considerations are key for any type of company. However, little is known about how companies consider moral objectives for their research and development (R&D) activities, or the basis upon which these activities are chosen. This research involves qualitative investigation into Responsible Research and Innovation (RRI) in the Information and Communication Technology (ICT) industry, comprising 30 in-depth, pan-European interviews with key personnel in the industry, and focus groups with employees at 14 different companies. Through investigation of the 'responsible' activities these companies currently undertake, we shed light on the types of moral goals they set and their underlying ethical standpoints. By reviewing both the responsible innovation and sustainability discourses, and presenting phenomenological evidence, we demonstrate that companies have adopted some aspects of RRI, even though it might not be recognised as such. Our findings indicate that these innovators recognise some of the ethical and societal concerns associated with their activities but their approach is often piecemeal; primary focus is upon the most immediate issues and on legal compliance, to the detriment of broader societal issues and wider challenges. We recommend explicit mechanisms that draw upon established ethical thought and practical academic work to improve companies' abilities to carry out their sustainability activities, and incorporate them into a responsible business strategy. We conclude with recommendations for innovators, corporate research and development, and policy. Graphical abstract: Image 1 Highlights: Private companies engage, to a limited extent, with responsible research and innovation (RRI). ICT companies demonstrate no aspirations to contribute towards grand societal challenges. Companies cannot rely upon market forces for dealing with the implications of their research and development (R&D) activities. Reflection upon the ethical underpinnings of research and innovation are vital for sustainability. Companies should clearly articulate and enact their moral aims and objectives.